Synthesis and characterization of new bent-core liquid crystal with a ferroelectric-like switching/modified magnetite nanocomposite - Ozkonstanyan, Aykun; Mert, Hatice Hande; Mert, Mehmet Selcuk; Eran, Belkiz Bilgin; Ocak, Hale (ELSEVIER, 2020)
A new bent-core liquid crystal (LC) compound 4-Cyano-1,3-phenylenebis[4-(4-(S)-2-Dodecyloxypropionyloxyphenoxycarbonyl)benzoate] (CyPDB) consisting of O-dodecyl lactate substituted terephthalate based rod-like units which were located at 1,3-positions of 4-cyanoresorcinol central unit has been synthesized and LC/1.0% modified Fe3O4 nanocomposite has been prepared. The effects of being the doped with 1.0% modified Fe3O4 (magnetite) nanoparticles on mesomorphic properties of the new bentcore liquid crystal, which exhibits an enantiotropic SmA phase with a ferroelectric-like switching, were investigated by differential scanning calorimetry, optical polarizing microscopy and electro-optic studies. The surface of Fe3O4 (magnetite) nanoparticles was modified with a silane surfactant, octadecyltrimethoxysilane (OTMS), used as a compatibilizer for the attractive interaction of liquid crystal molecule with Fe3O4 nanoparticles. The size, morphology and distribution of modified Fe3O4 (magnetite) nanoparticles in LC host were investigated by using Transmission Electron Microscope (TEM) and Scanning Electron Microscopy (SEM). The magnetic properties of nanocomposite were studied using a vibrating Sample Magnetometer (VSM). (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Bent-core liquid crystal; Fe3O4 (magnetite) nanoparticles; Lactate unit; Nanocomposite; ROD-LIKE; CHIRALITY; NANOPARTICLES; POLYMORPHISM; COMPOSITE; MOLECULE; MESOGENS; SERIES; PHASE; Chemistry